Visual Outcomes Following Surgical Treatment of Pituitary Adenomas: Functional Versus Non-Functional - Kulniwatcharoen, Pichaya; Piamjitchol, Chanakarn; Tangkitchot, Pavinee; Vaniyapong, Tanat; Unsrisong, Kittisak; Hansapinyo, Linda (Biomedical Sciences and Clinical Medicine, 2024)
Objective This study aims to compare visual outcomes following surgical resection of functional and non-functional pituitary adenoma. Methods A retrospective observational study included 103 patients with pituitary adenoma who underwent tumor resection at Chiang Mai university hospital between January 2010 and December 2019. Basic characteristics, tumor specific data, hormonal status and neuro-ophthalmic data were collected and statistically analyzed to identify differences in visual outcomes between functional and non-functional tumors. Results Between the 51 (49.50%) functional pituitary adenoma and 52 (50.50%) non-functional pituitary adenoma patients in this study, there were no differences in mean age at initial visit, sex, duration of onset, type of surgery, or adjunct radiotherapy. Initial visual acuity in logMAR in both the better and the worse eye, as well as the initial visual impairment score (VIS) which represents a combination of visual acuity and visual field, showed no statistically significant differences. The final visual acuity of the better eye was significantly better in the functional group (0.08± 0.15) than in the non-functional group (0.22±0.47), with a p-value of 0.04. Similarly, the VIS score was significantly better in the functional group (18.37±19.85) than in the non-functional group (28.87±26.83), with a p-value of 0.028. Conclusions Patients with functional pituitary adenomas have potentially better visual outcomes than those with non-functional pituitary adenomas after surgical resection.